Do the Right Thing! Leaders, Weather Shocks and Social Conflicts in Pre-Industrial France - Cédric Chambru (European Historical Economics Society (EHES), 2019)
I use spatial and temporal variation in temperature shocks to examine the effect of adverse weather conditions on the onset of social conflicts in seventeenth- and eighteenth-century France. The paper's contribution is threefold. First, I document the effect of temperature shocks on standards of living using cross-section and panel prices data. Second, I link high-resolution temperature data and a new database of 8,528 episodes of social conflicts in France between 1661 and 1789. I use a linear probability model with subregional and year fixed effects to establish a causal connection between temperature shocks and conflicts. One standard deviation increase in temperature increased the probability of social conflicts by about 5.3 per cent. To the best of my knowledge, these results are the first to quantify the effect of temperature shocks on intergroup conflict in pre-industrial Europe. Finally, I investigate the role of local leaders– the intendants– in the mitigation of temperature shocks. I show that leaders with higher level of local experience were better able to cope with adverse weather conditions. I argue that years of local experience were a key determinant in the intendant's ability to administer efficiently his province. This interpretation is supported by historical evidence.
Keywords: H12; N53; Q54; 330; Weather shocks; Institutions; Social Conflicts; Grain Prices; France; Ancien Régime